PENGARUH INTERDEPENDENSI MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN - Muktiyanto, Ali (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
This study aims to examine the effect of interdependence mechanisms of corporate governance on company performance (Agrawal and Knoeber 1996). These mechanisms are: managerial ownership, institutional ownership, independent commissioner, board size, debt policy, dividend policy, market concentration, and market share with the control variables are growth, size, and firm ages. Test results on 349 firm-years using OLS regression for each mechanism and 2SLS regression for simultaneous testing indicate the presence of interdependence between the mechanisms. both parsial and simultanously; managerial ownership and dividend policy does not significantly influence on the banking efficiency. Significant positive effect of the board size and institutional ownership when tested by OLS did not recur when tested simultaneously using 2SLS. Instead, the independent commissioner when tested by 2SLS have significant negative effect but using OLS no significant effect. There are three variables of corporate governance mechanisms have consistent effect on the banking efficiency; debt policy has significant negative effect, while the market concentration and market share have significant positive effect. Different results between the tests using OLS and 2SLS emphasize the interdependence of these mechanisms is also shown that application of the policy of corporate governance mechanisms should be done carefully so that the expected performance can be achieved.